Quantifying phytoplankton productivity and photoinhibition in the Ross Sea Polynya with large eddy simulation of Langmuir circulation. Issue 7 (10th July 2017) - Smyth, Robyn L.; Akan, Cigdem; Tejada‐Martínez, Andrés; Neale, Patrick J.
Abstract: Southern Ocean phytoplankton assemblages acclimated to low‐light environments that result from deep mixing are often sensitive to ultraviolet and high photosynthetically available radiation. In such assemblages, exposures to inhibitory irradiance near the surface result in loss of photosynthetic capacity that is not rapidly recovered and can depress photosynthesis after transport below depths penetrated by inhibitory irradiance. We used a coupled biophysical modeling approach to quantify the reduction in primary productivity due to photoinhibition based upon experiments and observations made during the spring bloom in Ross Sea Polynya (RSP). Large eddy simulation (LES) was used to generate depth trajectories representative of observed Langmuir circulation that were passed through an underwater light field to yield time series of spectral irradiance representative of what phytoplankton would have experienced in situ. These were used to drive an assemblage‐specific photosynthesis‐irradiance model with inhibition determined from a biological weighting function and repair rate estimated from shipboard experiments on the local assemblage. We estimate the daily depth‐integrated productivity was 230 mmol C m −2 . This estimate includes a 6–7% reduction in daily depth‐integrated productivity over potential productivity (i.e., effects of photoinhibition excluded). When trajectory depths were fixed (no vertical transport), the reduction in productivity was nearly double. Relative to LES estimates, there was slightly less depth‐integrated photoinhibition with random walk trajectories and nearly twice as much with circular rotations. This suggests it is important to account for turbulence when simulating the effects of vertical mixing on photoinhibition due to the kinetics of photodamage and repair. Plain Language Summary: Southern Ocean phytoplankton can be both limited and inhibited by sunlight. Models are needed to understand the full effect of sunlight on photosynthesis in the Southern Ocean. When mixing was deep and productivity was high in the Ross Sea Polynya, there was a small reduction in overall productivity due to exposure to high light during circulation near the surface. Key Points: Depth‐integrated productivity was estimated to be 230 mmol C m −2 d −1 during the spring bloom in the Ross Sea Polynya on a clear sky day with 6–7% reduction due to photoinhibition Deep vertical mixing beyond the euphotic zone mitigates the effects of photoinhibition on depth‐integrated primary production Light variation resulting from turbulent motions should be accounted for when estimating the effects of vertical mixing on depth‐integrated productivity